Creative leadership as a collective achievement: An Australian case. Issue 1 (February 2017) - Dovey, Ken; Burdon, Steve; Simpson, Robert
In this article, we examine the construct of 'leadership' through an analysis of the social practices that underpinned the Australian Broadcasting Corporation television production entitled The Code . Positioning the production within the neo-bureaucratic organisational form currently adopted by the global television industry, we explore new conceptualisations of the leadership phenomenon emerging within this industry in response to the increasingly complex, uncertain and interdependent nature of creative work within it. We show how the polyarchic governance regime characteristic of the neo-bureaucratic organisational form ensures broadcaster control and coordination through 'hard power' mechanisms embedded in the commissioning process and through 'soft power' relational practices that allow creative licence to those employed in the production. Furthermore, we show how both sets of practices (commissioning and creative practices) leverage and regenerate the relational resources – such as trust, commitment and resilience – gained from rich stakeholder experience of working together in the creative industries over a significant period of time. Referencing the leadership-as-practice perspective, we highlight the contingent and improvisational nature of these practices and metaphorically describe the leadership manifesting in this production as a form of 'interstitial glue' that binds and shapes stakeholder interests and collective agency.